Study of Banks’ Performance by Using RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital) Method - Nadirsyah Nadirsyah; Mirna Indriani; Dinaroe Dinaroe; Ismi Fadhliati (Proceedings of AICS - Social Sciences, 2018)
The study aims to examine the financial soundness between foreign exchange banks and non-foreign exchange banks by employing the RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital) method. The research population targeted is national private banks which are listed on the Indonesia Stock Exchange on 2010-2014 periods. 19 banks are selected as the sample and the period of observations is 5 years i.e. between 2010 and 2014 (95 observations). Data is collected from an annual report published in the central capital market reference at the Indonesia Stock Exchange. Mann-Whitney U test is used to analyze the data and test the proposed hypothesis. This study found no statistical financial soundness differences between the foreign exchange banks and non-foreign exchange banks.Keywords: financial soundness, risk profile, good corporate governance, earnings, capital.